Contraceptive Empowerment in adolescent mothers and young women. Systematic review - Luna Ferrales, Clarisa (2024)
Introduction: unplanned pregnancy in adolescence is a problem of global relevance, due to the consequences on adolescent mothers, their children and their families. Objective: analyze the scientific literature on contraceptive empowerment in adolescent mothers and young women. Methodology: systematic review of the literature, according to the PRISMA statement. We included articles indexed in MEDLINE/PubMed, Science Direct, Dialnet and Scielo were consulted, published through 2014 and 2021, in the language: Spanish, English and Portuguese that met the inclusion criteria, using keywords and Boolean AND/OR operators. Discussion: empowerment in reproductive health undoubtedly has repercussions on other aspects of women's lives, such as domestic and intimate partner violence, since when women are empowered, they are capable of making their own decisions. Results: a total of 16 articles were included, most of the studies included young women, they provided evidence on the characteristics of contraceptive empowerment in young women and adolescent mothers, in the use of antenatal services that promote the use of contraceptives, in the decision-making power in the prevention of first-time and subsequent pregnancy. The level of empowerment is directly related to the exercise of their sexual and reproductive rights; an empowered woman tends to use contraceptives more. Conclusions: contraceptive empowerment influences decision-making for sustained use of contraceptives in young women or adolescent mothers. It is necessary to generate